FIBROMATOSIS OF BREAST MIMICKING SARCOIDOSIS - Sachdeva, Silonie (Medknow Publications, 2011)
Primary mammary fibromatosis is a rare skin condition which can arise after trauma or previous surgery. The exact etiology is unknown. Very few cases have been reported in literature and the main emphasis is to differentiate this condition from breast carcinoma. We report here an unusual case of a 60 year old female who presented with skin lesion which clinically looked sarcoid with history suggestive of sarcoidosis, but on histopathology fibromatosis of breast was revealed. Complete work up ruled out any carcinomatous changes. Surgical excision of the lesion was done with no recurrence seen in one year follow up period.